Effect of Water Stress Condition on Architecture of Root Colonizing Arbuscular Mycorrhizal Fungi - Chaurasia, Bhaskar; Tripathi, Golden (International Journal of Computer Sciences and Engineering, 2025)
Availability of water is one of the important factor which determine the colonization of Arbuscular mycorrhizal fungus (AMF) in the roots of higher plant. Triticum aestivum plant is selected to study effect of water stress on root colonization pattern. Monocot plants are known for having 90% AMF colonization. AMF colonization pattern has been studies under drought condition, water logged condition and control condition. Under drought condition and control condition AMF colonization pattern is more or less similar while under drought condition AMF colonization percent is significantly reduced. AMF hyphal network and sporulation both are highly influence under water logged condition. Under drought condition sporulation was more in comparison to water logged and control condition. AMF colonization pattern was more extensive and prominent under drought conditions, while sporulation was comparatively low in waterlogged condition in comparison to drought condition. Various type of hyphal structures were also varied due to availability of water. Hypahl netwrok was more extensive and prominent under drought condition. Absorbing and runner hyphae extended quite long under drought condition in comparison to waterlogged condition. Appressoria formation was also prominent under drought condition. Under water logged condition only spores of Acaulospora species was found associated with the roots while under drought and control condition spores of Genus Glomus. Entrophospora and Acaulospora were found to associate with the roots. The results present study revealed that water is one of the important factor which regulated the colonization pattern of AM fungi.